DIFFERENCE TEST OF POTENTIAL LOSS FROM PROFIT SHARING FINANCING ISLAMIC BANKING IN INDONESIA - Taudlikhul Afkar; Fauziyah Fauziyah; Sigit Prihanto Utomo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Common problem with Islamic bank in Indonesia is the rate of return from financing business activities. Profit sharing financing is a type of business activity that still requires certainty in the distribution of profits and risks. The aim of this research is to conduct a different test analysis of potential loss for Islamic Bank in Indonesia from profit-sharing financing business activities during and after the Covid-19 pandemic. This research method uses a quantitative approach with a population of 14 Sharia Commercial Banks as the research sample. Saturated samples are used as a research sampling technique considering the small population size. The data analysis technique used in this research is Paired Sample t-test with Jamovi as an analysis tool. Findings of this research show that there is significant difference in potential losses in profit sharing financing during and after the Covid-19 pandemic with a tendency to be greater after the Covid-19 pandemic